Is Social Media Really the Answer? How Issues Create Communities and Communities Create Issues Online - Desai, R.; Wolf, Katharina (Deakin University Australia, 2014)
Public relations scholars have emphasised the role of the Internet, and in particular social media, as a new and effective way for communication professionals to engage with stakeholders on social issues. However, beyond conceptual papers, there has been limited to no empirical evidence that online spaces are indeed more effective when aiming to engage diverse, dispersed communities. This paper aims to address this gap, by examining the social media activities of two seemingly dissimilar communities: the Australian Asbestos Network and the West Australian Anti Nuclear Movement. The authors conclude that in an online advocacy context, communities create issues, as opposed to congregate around carefully crafted communications messages.